Provision of palliative and end-of-life care in UK care homes during the COVID-19 pandemic: A mixed methods observational study with implications for policy - Bradshaw, Andy; Ostler, Sophia; Goodman, Claire; Batkovskyte, Izabele; Ellis-Smith, Clare; Tunnard, India; Bone, Anna E.; Barclay, Stephen; Vernon, Martin; Higginson, Irene J.; Evans, Catherine J.; Sleeman, Katherine E. (Frontiers in Public Health, 2023)
Introduction Little consideration has been given to how the provision of palliative and end-of-life care in care homes was affected by COVID-19. The aims of this study were to: (i) investigate the response of UK care homes in meeting the rapidly increasing need for palliative and end-of-life care during the COVID-19 pandemic and (ii) propose policy recommendations for strengthening the provision of palliative and end-of-life care within care homes. Materials and methods A mixed methods observational study was conducted, which incorporated (i) an online cross-sectional survey of UK care homes and (ii) qualitative interviews with care home practitioners. Participants for the survey were recruited between April and September 2021. Survey participants indicating availability to participate in an interview were recruited using a purposive sampling approach between June and October 2021. Data were integrated through analytic triangulation in which we sought areas of convergence, divergence, and complementarity. Results There were 107 responses to the survey and 27 interviews. We found that (i) relationship-centered care is crucial to high-quality palliative and end-of-life care within care homes, but this was disrupted during the pandemic. (ii) Care homes' ability to maintain high-quality relationship-centered care required key “pillars” being in place: integration with external healthcare systems, digital inclusion, and a supported workforce. Inequities within the care home sector meant that in some services these pillars were compromised, and relationship-centered care suffered. (iii) The provision of relationship-centered care was undermined by care home staff feeling that their efforts and expertise in delivering palliative and end-of-life care often went unrecognized/undervalued. Conclusion Relationship-centered care is a key component of high-quality palliative and end-of-life care in care homes, but this was disrupted during the COVID-19 pandemic. We identify key policy priorities to equip care homes with the resources, capacity, and expertise needed to deliver palliative and end-of-life care: (i) integration within health and social care systems, (ii) digital inclusivity, (iii) workforce development, (iv) support for care home managers, and (v) addressing (dis)parities of esteem. These policy recommendations inform, extend, and align with policies and initiatives within the UK and internationally.